ニシ エンダービーランド ノ チガク ケンキュウ ケイカク ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 本吉, 洋一; モトヨシ, ヨウイチ; Motoyoshi, Yoishi (1994)
P(論文) 本研究小集会は, 南極観測第V期5カ年計画の地学分野の中心的研究プロジェクトである「東南極リソスフェアの構造と進化」(Structure and Evolution of East Antarctic Lithosphere : SEAL計画)の計画案策定のために開催された。計画の概要, 各研究分野の問題設定, 観測項目, 実施計画, 設営上の問題点, 国内での研究体制などについて活発な討論が行われた。 A Workshop "Earth Science Program in Western Enderby Land" was organized to discuss the future program of earth sciences in Enderby Land, entitled "Structure and Evolution of East Antarctic Lithosphere (SEAL Project)", which is proposed as part of the forthcoming 5-year scientific program of the Japanese Antarctic Research Expedition. This is a summary of the Workshop, including the outline of the whole project, scientific significance in earth sciences, detailed objects of survey and observation, logistical problems, and domestic organization of research. departmental bulletin paper